1933
DOI: 10.1021/ja01331a070
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements of Polyines. IV. Tetraphenyl-di-(3-methyl-3-ethylpentinyl-1)-ethane

Abstract: Vol. 55 hydrate upon phenylbromofluorene. With sodium in liquid ammonia solution, the hydrazo compound reacted to form a product, which, when hydrolyzed, yielded phenylfluorene. With various oxidizing agents, hydrazophenylfluorene yielded mainly phenylfluoryl peroxide.3. In experiments with palladium black, evidence was obtained for the possible momentary existence of azophenylfluorene; the compound, if formed, decomposed under the experimental conditions yielding nitrogen, phenylfluorene and dibiphenylenediph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1937
1937
1969
1969

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The work of Marvel and coworkers on the acetylenic ethanes (16,41,43,108,116,120) has shown that these rearrange readily into isomeric compounds without catalysts. Although the structure of these rearranged isomeric compounds has not been proven definitely, evidence supports the diolefin structure.…”
Section: -330mentioning
confidence: 99%
“…The work of Marvel and coworkers on the acetylenic ethanes (16,41,43,108,116,120) has shown that these rearrange readily into isomeric compounds without catalysts. Although the structure of these rearranged isomeric compounds has not been proven definitely, evidence supports the diolefin structure.…”
Section: -330mentioning
confidence: 99%